Pet fooled [videorecording (DVD)] - Harrington, Kohl, 1988- (Kino Lorber, 2017)
An in-depth exposé of the inner workings of the commercial pet food industry, raising questions into the nutritional quality and possible dangers of the products people use to feed their pets.